Unveiling Product Manager’s journey in software development: preliminary findings - Reis, Lucas; Rivero, Luis; Viana, Davi (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2024)
Depending on the company, the role of software product managers may have different responsibilities, but they often face similar challenges, and the necessary skills needed to solve them are usually the same. This paper evaluates the main problems faced by this role, as well as the necessary responsibilities and skills, to structure the journey of this professional through these three pillars. In addition, it is proposed to create a difference between the responsibilities of the Product Manager, Product Owner and Project Manager because these are roles with similar activities. A set of studies was created to verify the existing gaps in the area and a script of questions for interviews and online questionnaires, both run with professionals in the area. As preliminary results, we have the competency mapping prototype for the Product Managers’ journey, in addition to proposing elements that differentiate the three similar roles raised. We also obtained insights that were not observed in the literature. Our research contributes to the visualization of the Product Manager’s journey, offering new insights, understanding of functions and differences among these roles in the area.